The many faces of an income statement - SUWARDY, Themin (Institutional Knowledge at Singapore Management University, 2009)
When a company an- have no problem understandingnounces its financial the "nature" of this cost. However,results, most analysts if we were to allocate staff costs byand media coverage function, one would have to classitendto focus on its in- fy staff costs into all the functionscome statement, usually with of the entity, eg the wages of an emyear-on-yearor other periodic com- ployee working in the marketing deparisonsof performance.